Development of Digital Competence in the Training of Future Teachers in Ukraine and People's Republic of China - Tetyana M. Sobchenko (Mukachevo State University, 2021)
The relevance of the issue of forming digital competence of future teachers in higher education institutions is obvious, since technological progress is developing at an extremely rapid pace, and digitalisation has already penetrated into all spheres of life, including the education system. The purpose of this study is to compare the approaches of the state educational policy to the development of digital competence of future teachers in China and Ukraine. The following theoretical methods were used to obtain new results: analysis of pedagogical literature, regulatory documents, online platforms, educational sites, systematisation and generalisation of scientific research, organisation of training courses for future teachers - to compare different approaches to digital competence of future teachers. It is noted that digital competence is key in lifelong learning, as well as one of the components of a teacher's professional competence, according to the professional standard of primary school teachers and general secondary education teachers. The concept of digital competence is defined and it is proved that its significance changes in accordance with the development of digital modern society. The article analyses the state educational policy of Ukraine and China, in particular the regulatory framework regulating the development of digital competence in the countries. The issue of digital competence was discovered to be urgent in both countries, in particular in China, where its solution is carried out more progressively, due to powerful resource capabilities. An example of the content of academic disciplines is given, namely "digital training tools", "cybersecurity", "Media Education" (Ukraine), "fundamentals of computer use", "use of multimedia equipment" (China), their place in the educational process, hours to study, a form of control of educational and cognitive activity, etc. These academic disciplines are aimed at developing the digital competence of future teachers in higher education institutions of Ukraine and China. It is noted that further research will concern the study and analysis of the state educational policy of the European Union countries on the development of digital competence, in particular in the training of future teachers